(3QSGdI aj eUWdM GdMOjKs - (3YHO Gddg Hf Ydj Hf YHO GdQMef ShjOGf GdOedjLj,J (B1234 (3g` s
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf CeG HYO agPg fHPg ai HjGf eYGfi CbSGe GdMOjK Ydi hLg dWja hbO PcQJ KdGKjf bSekG GdbSe GdChd GdUMjM hgh eG QhGg GdYOd GdVGHW s
(3BNQgG (B:s
(3GdGYJHGQ hgh Cf jfXQ ai GdhGOi GdPi de jJGHY gd JGHY Ce dG hGddg JYGdi CYde HGdUhGH hEdjg GdeQLY hGdeBH s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B10s
(3GdfSNI HgG MhGTs
(3JUhas
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B107 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B89s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdeLGejYs